Anatomical variant origin of suprarenal arteries from coeliac trunk development, and its clinical significance - G., Vinitha; Parthasarthy, Meenakshi (International Journal of Research in Medical Sciences, 2020)
Background: One of the most vascular organ in the body Adrenal gland being highly variant in vasculature and tough to approach, its knowledge needs to be updated regularly. Anatomists, Surgeons and Radiologists will be benefitted with this study and improves the quality of care provided to patients by reducing morbidity and mortality. Methods: This study was done on 48 formalin fixed cadavers (33 males, 15 females) in the department of anatomy, between 2014-2019. Coeliac trunk was skeletonized, and branches traced looking for suprarenal arterial branches. Results: Superior Suprarenal Artery originated from Inferior phrenic artery in 13(27%) cases, and these Inferior phrenic arteries were arising from the Coeliac trunk, and in one (2.03%) case Superior suprarenal artery was arising directly from Coeliac trunk and which had even replaced the Middle Suprarenal Artery. None of the Middle and Inferior Suprarenal Artery came from coeliac trunk. Conclusions: Knowledge of Superior Suprarenal Arterial variations while doing surgeries, and during radiological interventions in and around the lesser sac, and involving the Coeliac trunk helps the clinicians in reducing the morbidity and mortality.